2016
DOI: 10.1038/srep29505
|View full text |Cite
|
Sign up to set email alerts
|

Biodiversity and Activity of the Gut Microbiota across the Life History of the Insect Herbivore Spodoptera littoralis

Abstract: Microbes that live inside insects play critical roles in host nutrition, physiology, and behavior. Although Lepidoptera (butterflies and moths) are one of the most diverse insect taxa, their microbial symbionts are little-studied, particularly during metamorphosis. Here, using ribosomal tag pyrosequencing of DNA and RNA, we investigated biodiversity and activity of gut microbiotas across the holometabolous life cycle of Spodoptera littoralis, a notorious agricultural pest worldwide. Proteobacteria and Firmicut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

33
331
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 313 publications
(369 citation statements)
references
References 51 publications
(65 reference statements)
33
331
5
Order By: Relevance
“…In adult H . erato , males and females share similar microbial communities (Hammer et al ., ), whereas in Spodoptera littoralis the sexes harbour divergent bacterial communities, with higher Enterobacteriaceae proportion found in females (Chen et al ., ). It is noteworthy that even when found, the consequences of sex‐dimorphic microbiota in Lepidoptera are not well understood.…”
Section: Discussionmentioning
confidence: 97%
“…In adult H . erato , males and females share similar microbial communities (Hammer et al ., ), whereas in Spodoptera littoralis the sexes harbour divergent bacterial communities, with higher Enterobacteriaceae proportion found in females (Chen et al ., ). It is noteworthy that even when found, the consequences of sex‐dimorphic microbiota in Lepidoptera are not well understood.…”
Section: Discussionmentioning
confidence: 97%
“…Traditional cultivation‐dependent technique for microorganism research was limited by numerous microorganisms that cannot be cultured now, and cannot reflect the alteration of microbiota community. However, the advent of amplicon sequencing offered us an insight of the entire community structure and those uncultured microorganisms (B. Chen et al, ; Cheung et al, ; Shao et al, ). More and more nonegligible roles of intestinal microflora were revealed by sequencing technology.…”
Section: Discussionmentioning
confidence: 99%
“…The previous study suggested that intestinal microflora was involved in human's physical and mental health (Petersen, Skov, Thyssen, & Jensen, ; Stricoff & Robinson, ). Similarly, intestinal microflora plays diverse functions in invertebrate, such as olfactory behavior regulation (Qiao, Keesey, Hansson, & Knaden, ), metabolism (Ayayee, Muñoz‐Garcia, & Keeney, ; B. Chen et al, ), and immune (Lee, Lee, & Lee, ; Martemyanov et al, ; Xia et al, ). In addition, consistent changes of gut microbial community and host development indicated that the gut microbiota might be involved in the entomic development (B. Chen et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, exposure to an environmental stress during an early life stage may later shape the initial colonizers at a later life stages and corresponding repertoire of microbial associates (e.g., amphibians: Kohl et al, 2013; insects: Hroncova et al, 2015; Chen et al, 2016; cnidarians: Fraune et al, 2016). These stage-specific influences on the physiology and survival of subsequent stages are referred to as carryover or latent effects (Pechenik et al, 1998; Pechenik, 2006).…”
Section: Host-associated Microbial Repertoirementioning
confidence: 99%